Pengaturan Pembagian Urusan Pemerintahan; Kritik Terhadap Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - Iza Rumesten; Helmanida Helmanida; Agus Ngadino (Universitas Sriwijaya, 2020)
Associated with the diversity of the region, not all matters relating to the diversity of the region are categorized in matters of choice, but it can also be considered obligatory, absolute government affairs public and government affairs. The problems discussed is how the criteria for the distribution of government affairs in the Law No. 23 Year 2014 on Regional Government. Based on the analysis, it can be concluded: first, more appropriately categorized cultural affairs affairs of choice, because it is a potential diversity of cultural affairs which is owned by the region. Second, the food matters more appropriately categorized as obligatory functions related to basic services.